Representation and identity in the wake of 9/11 : Khaled Hosseini’s The kite runner, Mohsin Hamid’s The reluctant fundamentalist, Frédéric Beigbeder’s Windows on the world and Don DeLillo’s Falling man - Andrews, Grant (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (English))--University of Stellenbosch, 2010.